Power quality enhancement in micro grids by employing MPC-EKF - Narender Reddy, N; Chandrasheker, O; Srujana, A (International Journal of Engineering and Technology, 2018)
This paper proposesdesign of a novel multi-level Control system based on Model Predictive Control Algorithm with Extended Kalman Filter (MPC-EKF) to enhance the power quality. The system utilized here implements few controllers based on MPC-EKF front end control, Top down control system and Bottom up control system to monitor periodic signals for fast sampling .TheMPC control divides the said problem into steady-state and transient sub problems individually and improves the response of the individual states .EKF traces the harmonics in the system improves power quality. The top down control system is responsible to improve the separated transient response and the bottom up control system is responsible to track the steady state error. Thus the proposed method is provided with the capability to enhance the quality of power and reliable performance of the microgrid by tracing and removing the harmonics in the distribution system, thereby decreasing the computational time. Our proposed method can be implemented on the MATLAB/SIMULINK plat form to validate the results.Â Â